2021
DOI: 10.1007/s11864-021-00866-9
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Treatment of Gastroenteropancreatic Neuroendocrine Carcinoma

Abstract: Opinion statementTreatment recommendations for advanced gastroenteropancreatic neuroendocrine carcinomas (GEP-NEC) are based on uncontrolled, mainly retrospective data. Chemotherapy can offer palliative relief, but long-lasting complete responses or cures are rare. The European Neuroendocrine Tumour Society (ENETS) and European Society for Medical Oncology (ESMO) recommend platinum-based chemotherapy as first-line treatment. This has been the golden standard since the late 1980s and has been evaluated in mostl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 91 publications
1
14
0
Order By: Relevance
“…[16,20,26] The average or median age at the time of diagnosis ranges from 50 to 70 years in different studies. [5][6][7]14,[26][27][28] Our patient was 57 years of age and fell within this age range. As expected, the patient had metastatic disease Approximately two-thirds of the cases were metastatic at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[16,20,26] The average or median age at the time of diagnosis ranges from 50 to 70 years in different studies. [5][6][7]14,[26][27][28] Our patient was 57 years of age and fell within this age range. As expected, the patient had metastatic disease Approximately two-thirds of the cases were metastatic at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with metastatic CRNEC with deficient mismatch repair (dMMR), high microsatellite instability (MSI-H), and BRAF mutation, addition of immune checkpoint inhibitor therapy is recommended. [ 16 , 19 , 26 , 29 , 44 , 49 ] Our patient received such therapy but did not undergo a tumor cell molecular study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the efficacy and longlasting response of platinum-based chemotherapy (etoposide and cisplatin/carboplatin, EP/EC regimens) is very limited. The reported objective response rate (ORR) ranges from 20% to 40%, with a median progression-free survival (PFS) of 2-6 months and an overall survival (OS) of 6-12 months (7). In the NORDIC NEC study, investigators retrospectively analyzed 305 patients with advanced gastrointestinal NEC and found that the ORR of the first-line platinum-based chemotherapy was 31%, with a median PFS of 4 months (95% confidence interval (CI) 3.1-4.6 months) and a median OS of 11 months (95% CI 9.4-12.6 months) (8).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with G3 NETs or Ki-67 < 55% (mostly well-differentiated) were significantly less responsive to treatment than those with NEC or Ki-67 ≥ 55% (mostly poorly differentiated). G3 NET and NEC patients have an objective response rate (ORR) of less than 17% and 35%-70%, a median progression-free survival rate (mPFS) of 2.4-4 mo and 5.0 mo, and mOS of 17 mo and 99 mo, respectively[ 8 - 10 ].…”
Section: Introductionmentioning
confidence: 99%